Transdiagnostic CBT for adult emotional disorders: A feasibility open trial from Saudi Arabia. (2019) - Alatiq, Yousra; Al Modayfer, Omar
Abstract: : Transdiagnostic cognitive behavioural therapy (T-CBT) provides potential for improving psychotherapy services in countries with limited resources. The primary aim of this study was to assess the feasibility and potential benefits of using T-CBT in Saudi Arabia to treat adult emotional disorders in a naturalistic open trial. A secondary aim was to measure the effect of this approach when delivered by junior psychologists as a low-intensity intervention. The overall sample consisted of 198 patients (160 in the low-intensity group). Only 33 (16.7%) patients had completed the treatment plan, 55 (27.3%) were still active in treatment, and 109 (55%) had disengaged from the treatment. The pre- and post-assessments for the clients who completed the treatment showed a significant decrease in all outcome measures. This result held true for the whole sample and the low-intensity group. This study provides initial evidence that T-CBT is suitable for clients with emotional disorders in Saudi Arabia. The study also provides support for the effect of T-CBT as a low-intensity intervention delivered by junior psychologists. However, one of the study limitations was the sample size for the group who completed the treatment and was properly discharged from service. Implications and recommendations are discussed. Key learning aims: (1) To examine the feasibility and potential benefits of using T-CBT in Saudi Arabia. (2) To measure the effect of T-CBT as low-intensity interventions delivered by junior psychologists. (3) To establish evidence-based practice for T-CBT in Saudi Arabia.